Profile, motivational factors and job satisfaction of special librarians in Metro Manila - Roque, Norma M.; Yang, Jackson V.; Santos, Herminia H. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2001)
Being in the era of globalization, organizations today adapt to the many changes around them. In librarianship, libraries and librarians are coping with the changes most especially in the emerging technologies. Thus, their interest to work willingly, effectively and efficiently to achieve their organization's goals must be improved. Librarians, just like any other professionals or employees should be properly motivated to improve their job satisfaction. This study assessed the level of motivation and the degree of job satisfaction among special librarians in Metro Manila and the effect or influence of the different personal and work-related characteristics on their job satisfaction.
Special librarians from different government and private agencies who are members of the Association of Special Libraries of the Philippines (ASLP) in Metro Manila and who had participated in the ASLP's training and seminars from the year 1997 - 1999 were considered in this study. Among the 167 considered in the study, 148 (88.6 percent) participated.
Descriptive method of research was used to determine the nature of the prevailing conditions and practices. A three-part survey questionnaire was used to collect data. Part I is about the personal characteristics of the special librarians such as gender, civil status, age, and educational attainment as well as their work-related characteristics such as type of library, length of service and salary. Part II is the Factors Important In My Job (FIMJ) Instrument. This measured the level of motivation and degree of satisfaction of the special librarians. Part III is the instrument used to identify the operating level of the special librarians based on Maslow's Hierarchy of Needs Theory.
Collected data were analyzed using the Statistical Package for Social Science (SPSS). Percentages, mean, standard deviation were used to compute the responses for demographic variables and describe respondents' characteristics. Chi-square, analysis of Variance (ANOVA) and linear regression were used to determine the difference in the perception of respondents when they were grouped according to some selected variables such as gender, age, civil status, type of library, educational attainment, length of service and salary.
Data obtained from the study showed that the actual level of job motivation and job satisfaction of the special librarians in Metro Manila is Very Good while their desired and valued level are both Excellent. Age, gender, educational attainment, monthly salary, length of service and type of library affect job satisfaction of the special librarians in Metro Manila, thus the null hypotheses were rejected. Differences were found in young special librarians who tend to be more satisfied than older librarians.
This study confirmed the results of previous studies that claim job satisfaction is influenced by age, educational attainment, civil status, type of library, length of service and salary. Several recommendations were given to improve the actual level of job satisfaction of the special librarians and to boost their morale being one of the newly recognized professionals in the Philippines.
Vita.
Special Problem (Master of Library Science)
Keywords: Association of Special Librries of the Philippines; Special librarians -- Job satisfaction -- Philippines -- Manila Metropolitan Area; Special libraries -- Philippines -- Manila Metropolitan Area